Pengarusutamaan Gender Di Kelurahan Klojen MelaluiPemberdayaan: Bincang Santai Mahasiswa HKn FIS Universitas Negeri Malang SDGs - Anggun Islami Putri; Attalah Rafif Widyadhana; Helena Putri Widyawati; Nurul izkiyah; Zidny Tsabita Fahmi; Sri Untari (PT Polstac Repositori Riset, 2025)
Gender equality and justice is a condition where the portion and social cycle of women and men are equal, balanced and harmonious. Gender equality seeks how men and women have the opportunity to realize their rights and potential to contribute to political, economic, social, and cultural development, and can equally enjoy the results of that development The research method used was a qualitative approach with a case study in Klojen Village. Primary data was obtained through interviews with women participating in government, community leaders, and organizers of health and empowerment programs. Secondary data came from policy documents and previous research. Data analysis techniques were conducted thematically to identify patterns and factors that contribute to increasing women's participation. Indonesia still has challenges to face in terms of women's economic participation, health, education, and political representation. Of course, this is a big responsibility for the Indonesian government that has just changed, because if seen from the Global Gender Gap Report data, it shows that gender equality in Indonesia in 2024 is still at a score of 68.6% of the average global gender equality score set in 2024 which is 68.5%, this figure is observed to be 0.01% higher than the global average. The amount of increase can be used as an indicator that the number of people's awareness of gender equality is still minimal.